Description of a new species of Microhyla from Bali, Indonesia (Amphibia, Anura) - Matsui, Masafumi; Hamidy, Amir; Eto, Koshiro (Zootaxa, 2013)
We describe a microhylid frog from Bali, Indonesia as a new species, Microhyla orientalis sp. nov. It belongs to the M. achatina group and is close to M. mantheyi, M. malang, and M. borneensis. It is distinguished from its congeners by a combination of the following characters: small size (adult males about 16–17 mm in SVL); a faint vertebral stripe present; a black lateral stripe from behind eye to half length of trunk; snout rounded in profile; eyelid without supraciliary spines; first finger less than one-fifth of third; tips of three outer fingers weakly dilated, forming weak disks, dorsally with median longitudinal groove; outer palmar tubercle single; tibiotarsal articulation reaching up to center of eye; tips of toes distinctly dilated into disks, dorsally with median longitudinal groove; inner and outer metatarsal tubercles present; four or more phalanges on inner and outer sides of fourth toe, and three phalanges on inner side of fifth toe free of web; and tail of larva with a black marking at middle. The male advertisement call of the new species consists of a series of notes each lasts for 0.01−0.08 s and composed of 3−5 pulses with a dominant frequency of 3.2–3.6 kHz. Uncorrected sequence divergences between M. orientalis and all homologous 16S rRNA sequences available were >6.6%. At present, the new species is known from rice fields between 435–815 m elevation in Wongaya Gede and Batukaru.